2007
DOI: 10.1177/039463200702000215
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine Synergizes with Oseltamivir in Protecting Mice from Lethal Influenza Infection

Abstract: Many studies have shown that oxidative stress is important in the pathogenesis of pulmonary damage during influenza virus infections. Antioxidant molecules are therefore potentially useful against viral infection. Our previous studies show that N-acetylcysteine (NAC) has a protective effect in a model of lethal influenza infection in mice. NAC administration significantly decreased the mortality in infected mice. Further studies have demonstrated that NAC enhanced survival in combination with the antiviral age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 36 publications
4
56
0
5
Order By: Relevance
“…Furthermore, a combination of NAC and oseltamivir also synergistically reduced the lethal effect of influenza virus infection in mice [51]. These results support the notion that combinations of antioxidant therapy with current drugs can improve the treatment of influenza virus infections.…”
Section: Superoxide Dismutasessupporting
confidence: 74%
“…Furthermore, a combination of NAC and oseltamivir also synergistically reduced the lethal effect of influenza virus infection in mice [51]. These results support the notion that combinations of antioxidant therapy with current drugs can improve the treatment of influenza virus infections.…”
Section: Superoxide Dismutasessupporting
confidence: 74%
“…Antioxidant molecules including reduced glutathione and its precursor N-acetyl-Lcysteine (NAC) are potentially useful against infection with influenza A viruses [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence of involvement of nitrosative stress in influenza A is the demonstration of strong 8-nitroguanosine immunostaining in the cytosol of bronchial and bronchiolar epithelial cells of influenza virus-infected wild-type mice but not iNOS-deficient mice [15]. Moreover, a number of studies have demonstrated that reactive oxygen species contribute to the exacerbation of lung inflammation and lethality in influenza-infected mice, while the use of glutathione precursor promotes survival in influenza-infected mice [16,17]. The results reported in this work are in agreement with those of a study by Li et al, who demonstrated a 2.4-fold increase in nitric oxide production in patients infected with influenza A [8], and also showed that the production of nitric oxide in pdmH1N1 was significantly less than that of seasonal influenza A.…”
Section: Discussionmentioning
confidence: 99%